Aspectos metrológicos na estimativa da atividade administrada em pacientes de medicina nuclear - Anelise Ruzzarin; Ana Maria Xavier; akira Iwahara; Luiz Tahuata (Brazilian Journal of Radiation Sciences)
In order to investigate the performance quality of routine measurements of Nuclear Medicine Services (NMS), the National Metrology Laboratory of Ionizing Radiation/Institute of Radiation Protection and Dosimetry (LNMRI/IRD) has been conducting, since 1998, a program of comparison for activity measurements of radiopharmaceuticals administered to patients in nuclear medicine. Correction factors are determined from the result of performance analysis in order to determine with better accuracy the activity to be administered to the patients.